Genomic surveillance of Escherichia coli ST131 identifies local expansion and serial replacement of subclones. Issue 4 (26th April 2020) - Ludden, Catherine; Decano, Arun Gonzales; Jamrozy, Dorota; Pickard, Derek; Morris, Dearbhaile; Parkhill, Julian; Peacock, Sharon J.; Cormican, Martin; Downing, Tim
Abstract : Escherichia coli sequence type 131 (ST131) is a pandemic clone that is evolving rapidly with increasing levels of antimicrobial resistance. Here, we investigated an outbreak of E. coli ST131 producing extended spectrum β-lactamases (ESBLs) in a long-term care facility (LTCF) in Ireland by combining data from this LTCF ( n =69) with other Irish ( n =35) and global ( n =690) ST131 genomes to reconstruct the evolutionary history and understand changes in population structure and genome architecture over time. This required a combination of short- and long-read genome sequencing, de novo assembly, read mapping, ESBL gene screening, plasmid alignment and temporal phylogenetics. We found that Clade C was the most prevalent (686 out of 794 isolates, 86 %) of the three major ST131 clades circulating worldwide (A with fimH41, B with fimH22, C with fimH30 ), and was associated with the presence of different ESBL alleles, diverse plasmids and transposable elements. Clade C was estimated to have emerged in c . 1985 and subsequently acquired different ESBL gene variants ( bla CTX-M-14 vs bla CTX-M-15 ). An ISEcp 1- mediated transposition of the bla CTX-M-15 gene further increased the diversity within Clade C. We discovered a local clonal expansion of a rare C2 lineage (C2_8) with a chromosomal insertion of bla CTX-M-15 at the mppA gene. This was acquired from an IncFIA plasmid. The C2_8 lineage clonally expanded in the Irish LTCF from 2006, displacing the existing C1 strain (C1_10), highlighting the potential for novel ESBL-producing ST131 with a distinct genetic profile to cause outbreaks strongly associated with specific healthcare environments.